HUBUNGAN KOMPETENSI PETANI DENGAN PENDAPATAN USAHATANI BAWANG MERAH (Allium ascalonicum L.) (Kasus di Desa Mulyasari Kecamatan Losari Kabupaten Cirebon) - Achmad Faqih (Universitas Galuh, 2022)
The success of farmers in managing their farming, especially shallot plants is largely determined by the competence of farmers in conducting onion cultivation, because competence is a basic trait of a person which is itself related to the implementation of a job effectively and efficiently, as well as a combination of knowledge, skills, values and abilities. an attitude that is reflected in the habit of thinking and acting. This study aims to determine: (1) the relationship between knowledge competence and farm income, (2) the relationship between the attitude competence of farmers and farm income, and (3) the relationship between farmer skills competence and onion farming income. The research was conducted in Mulyasari Village, Losari District, Cirebon Regency. The research was conducted from October to December 2020. The research design used in this study was a quantitative study, with a descriptive survey research technique. Primary data collection was obtained through interviews with respondent farmers using a list of questions, and secondary data obtained from agencies related to this research. To determine the relationship between farmer competence and farmer income, the Spearman level correlation test was used. The results showed that: (1) there was a moderate and significant relationship between farmer knowledge and onion farming income, with a value of rs = 0.560 and a t-value of 5.060, (2) there was a moderate and significant relationship between farmer attitudes and onion farming income. red, with a value of rs = 0.544 and a tcount of 4.850, and (3) there is a moderate and significant relationship between farmer skills and onion farming income, with a value of rs = 0.550 and a t-value of 4.927.